2022
DOI: 10.1155/2022/3363830
|View full text |Cite|
|
Sign up to set email alerts
|

The Connection between High Myopia Patients and MiR-708a or MiR-148 Expression Levels in Aqueous Studies of Visual Acuity

Abstract: Myopia goes far beyond the inconvenience it brings. It is a prevailing and vision-threatening eye disease, especially in Asia. Aberrantly expressed miR-708a and miR-148 are critical for accurate diagnosis, good prognosis, and precise response prediction of myopia. In this paper, we aim to examine the potential contributions of miR-708a, miR-148a, and PAX6 to high myopia (HM). First, aqueous samples were taken from 25 exclusively HM eyes and 25 exclusively cataract eyes. For next-generation sequencing and bioin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Non-coding RNAs include microRNAs (miRNAs), repetitive RNAs, intronic RNAs, and long non-coding RNAs (lncRNAs), which are a diverse group of biomolecules with broad potential to control gene expression [ 53 ]. It is shown that mmu-mir-1936, mmu-mir-338-5p, mmu-mir-673-3p [ 54 ], miR-328 [ 55 ], miR-708a, and miR-148 [ 56 ] are related to myopia and can be used as biomarkers of myopia. MicroRNA-29a may affect myopia development by regulating type I collagen [ 57 ].…”
Section: Heredity and Myopiamentioning
confidence: 99%
“…Non-coding RNAs include microRNAs (miRNAs), repetitive RNAs, intronic RNAs, and long non-coding RNAs (lncRNAs), which are a diverse group of biomolecules with broad potential to control gene expression [ 53 ]. It is shown that mmu-mir-1936, mmu-mir-338-5p, mmu-mir-673-3p [ 54 ], miR-328 [ 55 ], miR-708a, and miR-148 [ 56 ] are related to myopia and can be used as biomarkers of myopia. MicroRNA-29a may affect myopia development by regulating type I collagen [ 57 ].…”
Section: Heredity and Myopiamentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%